Hyponatremia with Rhabdomyolysis - Unusual Presentation of Pituitary Apoplexy (Journal of Medicine, 2019)
Hyponatremia is increasingly being identified among hospitalized patients. It significantly alters outcome either by itself or by inappropriate correction. We report a 29-year-old man, who presented to the out-patient services with headache of 1 week and projectile vomiting of 2 days. He also had cramps in calf since a day. Had no fever and had received intramuscular injection for calf pain. Clinical examination including fundoscopy were normal except for irritability and calf tenderness. Blood chemistry and haematology were normal, except for hyponatremia (110 m Eq/L) and elevated CPK (creatine phosphokinase). SIADH was considered as he was euvolemic with low serum osmolality and high urine osmolality. Further evaluation showed hypoadrenalism and hypothyroidism suggestive of hypopituitarism. Subsequent MRI of sella revealed a 1 cm3 cystic mass with features of haemorrhage. Pituitary apoplexy with hypopituitarism was definitive, considering the acute presentation. Supplementation of steroids and thyroxine along with sodium correction improved him symptomatically. Trans-sphenoidal resection of the sellar cystic lesion was performed. Often a good clinical history, assessment and judicious investigations can identify the cause for hyponatremia. Rhabdomyolysis is known to occur in severe hyponatremia and adrenal insufficiency as with the present case. In literature, there are reports of pituitary apoplexy presenting with rhabdomyolysis and hyponatremia. Pituitary apoplexy is a medical emergency which requires early identification, hormonal supplementation and supportive care for better outcome.J MEDICINE JUL 2019; 20 (1) : 49-51